Propagation prediction based on measurement at 5.8GHz for fixed wireless access - Tang, Min Keen; Abdul Rahman, Tharek (Springer Berlin / Heidelberg, 2004)
This paper reviews most commonly used ray tracing techniques and applies a ray tracing technique which incorporates site specific environmental data to predict path loss in newly constructed hostels in Universiti Teknologi Malaysia (UTM) for 5.8 GHz Industrial, Scientific and Medical (ISM) band in Malaysia. Radio propagation path loss has been measured in order to verify the predicted results. As the prediction model excluding the vegetation affects that appeared in the fresnel zone clearance in the real site environment [3], corrections has been done on the predicted total loss in taking account the obstruction loss. It indicates a good agreement between measurements and predicted result with a deviation range of 0.01 dB to 2.82 dB.